2010
DOI: 10.1016/j.vetimm.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and antibody responses in sheep after primary and secondary experimental challenges with the mange mite Sarcoptes scabiei var. ovis

Abstract: In this work the clinical evolution and the specific serum IgG and IgE antibody responses in sheep after primary (n=10) and secondary (n=4) experimental challenges with the mange mite Sarcoptes scabiei var. ovis were studied. The primary infection was characterized by the development of mange lesions in all sheep, a detection of live S. scabiei mites in 70% skin scrapings taken in week 10 post-challenge (PC), strongly raised and sustained specific IgG levels and a more moderate but continuous rise in specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…A lack of IgE binding during primary infestation was observed in a significant proportion of S. scabiei infected dogs [27] and sheep [56], whereas in another study goats mounted a strong IgE responses to both primary and repeated mite challenge [46]. IgE responses also increased significantly in sheep during secondary infestation [56].From this it appears that differences may exist between the immune responses of humans and other animals to scabies, and between primary and secondary infestations. Thus, future ELISA design should consider the possibility of using different secondary antibodies for diagnosis in medical and veterinary settings.…”
Section: Discussionmentioning
confidence: 88%
“…A lack of IgE binding during primary infestation was observed in a significant proportion of S. scabiei infected dogs [27] and sheep [56], whereas in another study goats mounted a strong IgE responses to both primary and repeated mite challenge [46]. IgE responses also increased significantly in sheep during secondary infestation [56].From this it appears that differences may exist between the immune responses of humans and other animals to scabies, and between primary and secondary infestations. Thus, future ELISA design should consider the possibility of using different secondary antibodies for diagnosis in medical and veterinary settings.…”
Section: Discussionmentioning
confidence: 88%
“…A variety of immunoblotting studies have reported the molecular weights of various antigens recognized by the antibodies in the serum from scabies-infested hosts Arlian et al 1996aArlian et al , 2004aMorgan et al 1997;Arlian and Morgan 2000;Schumann et al 2001;Tarigan and Huntley 2005;Yadav et al 2006;Zalunardo et al 2006;Casais et al 2007;Rambozzi et al 2007;Rodriguez-Cadenas et al 2010;Hejduk et al 2011;Jakubek et al 2012). Yet little data identifying the proteins involved have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely high levels of IgE antibody have been reported in patients with crusted scabies, indicative of a Th2-biased immune response (5,6,15,32). However, studies in goat and sheep models suggested that high IgE levels may indicate protective immune responses (33,34), and thus high levels of IgE may therefore not be directly related to a dysregulated immune response leading to the development of crusted scabies. PBMCs isolated from patients with crusted scabies secreted higher levels of IL-4, IL-5 and IL-13 and lower levels of IFNc compared with those of ordinary scabies patients (15).…”
Section: Discussionmentioning
confidence: 99%